COVID-19 in Patients with Different Hematological Malignancies: Treatment Strategy and Outcome: An Iraqi Experience - Naji, Alaadin Sahham; Barwari, Zeki Ali Mohamed; Al-Khero, Khalid N.; Yassin, Ahmed Kh.; Saleh, Tareq A.; Tawfiq, Shwan Ali; Rashid, Nawshirwan Gafoor; Hasan, Kawa Muhamedamin; Mohamed, Amer Shareef; Al Qayyim, Mohammed Kamil; Al-Ani, Abdulsalam; Alwan, Alaa Fadhil (Jordan Medical Journal, 2024)
Background: Patients with hematological malignancies may have higher rates of morbidity and mortality due to SARS-COVID-19 than those in the general population. Objectives: To evaluate the outcome of SARS-COVID-19 in patients with different hematological malignancies undergoing active or modified therapy. Settings: This was a retrospective cohort, multicenter study conducted on 167 patients diagnosed with SARS-COVID-19. The selected patients had been diagnosed with different hematological malignancies and had received treatment (chemotherapy or immunosuppressive). The study was carried out in different centers across Iraq between 1 December 2020 and 1 December 2021. Patients and Methods: This study was conducted in seven hematology centers across Iraq with 167 patients; of these, this study showed that 88 (52.7%) were males and 79 (47.3%) were females (mean age 51.9 ± 18.3 years). All patients had had a COVID-19 infection confirmed through RNA-specific fragments by real-time reverse transcriptase polymerase chain reaction (RT-PCR) of the nasopharyngeal swab specimens, and by computed tomography (CT) of the chest. Demographic data were obtained from patient files, which included the type of hematological malignancy, treatment (chemotherapy, immunotherapy, supportive), severity of COVID-19, modification of treatment and disease outcome for patients, whether alive or not. Patients identified as having benign or non-hematological malignancies were excluded. Results: The treatment protocol was modified in 124 patients (74.3%), while 43 patients (25.7%) continued on the same protocol. Regarding treatment outcomes, 77.2% of patients were alive at the end of the study and 22.8% had died. The survival of COVID-19 patients did not change significantly when the treatment protocol was modified compared to those who continued on treatment as per protocol. The death rate was significantly higher among patients with severe disease compared to those with mild and moderate disease (61.4% v. 0% and 5.0%, respectively) (p<0.001). Conclusions: The management of patients with hematological malignancies during the COVID-19 pandemic may be challenging, with higher mortality in patients with concurrent hematological malignancies and COVID-19. The survival of COVID-19 patients did not change significantly when treatment was modified. Age groups, sex, type of hematological malignancy, and disease status did not affect the survival of these patients. The death rate was significantly higher among patients with hematological malignancies and severe COVID-19 compared with mild or moderate disease.